Pelatihan Pengukuran Dan Perhitungan Tonase Kapal Berdasarkan Peraturan Menteri Perhubungan No. PM 45 Tahun 2021 Pada Perajin Kapal Kayu Tradisional Di Kecamatan Galesong Kabupaten Takalar - Wahyuddin Mustafa; Syamsul Asri; Farianto Fachruddin L; Moh. Rizal Firmansyah; Misliah .; Rosmani .; Hamzah .; Fadhil Rizki Clausthaldi; Wihdat Djafar; Wishal Wijdan A.N (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
The basic idea of ​​tonnage measurement is to determine the capacity and withdrawal of levies of a ship, which then develops into proof of ship ownership and the ship's nationality. In 1969, a conference was held regarding the measurement of ship tonnage, known as Tonnage Measurement of Ship (TMS) 1969. This rule was enacted internationally in 1982 and ratified by the Republic of Indonesia in 1989. As a form of ratification commitment, the Republic of Indonesia has regulations outlined in Law No. 17 of 2008 concerning shipping, Government Regulation No. 51 of 2002 concerning shipping, and Minister of Transportation Regulation Number PM 45 of 2021 concerning ship measurements. Regulation of the Minister of Transportation Number PM 45 of 2021 concerning ship measurements is a new regulatory product. Hence, it is necessary to disseminate the regulation to the community of traditional ship owners and craftsmen. The dissemination was conducted in the Galesong District for a group of wooden boat craftsmen, TORANI, in the form of training in measuring and calculating wooden boat GT (gross tonnage) and NT (net tonnage) using domestic methods. During the training, participants showed high enthusiasm and enthusiastically asked questions about these regulations, including how to measure the GT and NT of a boat. The Training Success Indicator (IKP) is 85%, obtained from the average post-test score. The indicator percentage shows that the training was satisfactory in delivering the new regulation to the participants.